Evaluating Transitional Justice
XII, 293 p.
Keywords: This major study examines the successes and failures of the full transitional justice programme in Sierra Leone. It sets out the implications of the Sierra Leonean experience for other post-conflict situations and for the broader project of evaluating transitional justice.